Antibacterial, Antibiofilm, and Anti-Quorum Sensing Potential of Novel Synthetic Compounds Against Pathogenic Bacteria Isolated From Chronic Sinusitis Patients - Muhammad Asif Rafiq; Muhammad Shahid; Kashif Jilani; Muhammad Aamir Aslam (SAGE Publishing, 2022)
Quorum sensing (QS) is a major controller of virulence and biofilm formation in pathogenic bacteria. The aim of the research was to screen novel synthetic compounds (18) from 2 series (Pyrazole and Diene dione) for quorum sensing and biofilm inhibitory potential against resistant pathogens isolated from patients with chronic sinusitis. Most of the compounds have documented zone of inhibition against Gram positive strains Staphylococcus aureus , Enterococcus faecalis and moderate activity against Gram negative Klebseilla pneumoniae and Proteus mirabilis in comparison with standard antibiotic. Compounds Q1 and Q7 have given the maximum zone of inhibition 18 and 20 mm with MICs 0.312 mg/mL and .156 mg/mL against S aureus and E faecalis, respectively. Some compounds were equally potent at inhibiting the formation of biofilm which later established by phase contrast microscopy. Regarding quorum sensing inhibition, the tested concentration of synthetic compound UA3 0.313 mg/mL inhibited violacein production without decreasing Chromobacterium pseudoviolaceum count which was significantly lower than determined MIC's. It was depicted from the results that selected compounds exhibited low level of cytotoxicity toward human red blood cells. Hence, these findings revealed that most novel compounds were effective antibacterial, whereas compound UA3 has shared significant anti-quorum sensing potential against Chromobacterium pseudoviolaceum.